Location sensing to manage identity risk - Smeeton, Richard (2014)
This project proposes that correlating location sensing data obtained from mobile devices with cloud-based identity management services provides a novel and potentially valuable opportunity to reduce risk of identity theft and associated fraud. Location information is readily provided by mobile devices through a combination of global positioning, wireless triangulation and IP address association. These data may therefore serve as additional authentication factors during posture assessment of credentials, simplifying access whilst at the same time increasing security. The research analyses the scientific and business potential to develop the use of location as an additional security factor in identity management (IDM). Analyst research by Forrester (Cser, 2014) identified a number of potential gaps in the current IDM market, and this report highlights potential ways these could be exploited. Whilst there are some emerging examples of location being used to manage card payment risks, and many identity service providers, this research identifies an unmet market need for an affordable and scalable consumer solution that mitigates the increasing risks of identity theft, specifically by using location as an additional factor and doing so in the cloud. The market opportunity to develop an enterprise solution is also examined. The project also undertakes analysis of the potential to protect the Intellectual Property of these ideas, and includes a business plan with options to transfer and commercialise the technology being presented. The analysis of the report included: WIN2, SWOT, financial, competitor; and market insight/market access in cloud based identity management. Providing extensive insight into the market opportunities, strategic recommendations are made to transfer the technology into a viable commercial offering, either by licensing the technology for development by third parties, a possible joint venture, or by launching an independent start-up company.